Peritoneal Malignant Mesothelioma Metastatic to Supraclavicular Lymph Nodes. (September 2014) - Zannella, Stefano; Testi, Maria Adele; Cattoretti, Giorgio; Pelosi, Giuseppe; Zucchini, Nicola
Distinguishing between malignant mesothelioma and reactive mesothelial hyperplasia is often inestimable, but may be a challenging gauntlet for pathologists. A 62-year-old man underwent appendectomy after the identification of a peritoneal mass and the histological examination showed mesothelial proliferation along the appendix surface with no clear images of infiltration. After a few months the patient developed mediastinal and supraclavicular lymphadenopathies, and a nodal biopsy showed mesothelial cell proliferation invading lymphatic sinuses, consistent with the cells seen in the abdominal cavity. Since overt morphologic criteria for malignancy were lacking and reactive mesothelial cell deposits have been documented in lymph nodes, a molecular investigation of the CDKN2A (henceforth simply p16) gene status via fluorescence in situ hybridization was performed, which showed homozygous deletion in 100% tumor cells. These data ruled out the hypothesis of reactive mesothelial cells inclusion in lymph nodes, thus confirming the diagnosis of epithelioid malignant mesothelioma.